Pemberdayaan Kader dalam Penggunaan Media Bermain Sederhana sebagai Upaya Stimulasi Perkembangan Anak Usia Pra Sekolah - Riska Arsita Harnawati; Nora Rahmanindar; Meyliya Qudriani; Intan Cristy Mayasari Rizqi (Jurnal Surya Masyarakat, 2024)
Play media is essential for fostering interaction and growth in children. In children, the prevalence of movement abnormalities is 30.9% and speech development disorders 46.8%. The presence of electronics enhances this danger; children who play with them for thirty minutes have a forty-nine percent higher chance of speaking and moving late in life. Targeting Integrated Healthcare Center cadres, activities were conducted in Pagongan Village, Tegal Regency. The purpose of this community service project is to broaden the cadres' understanding of basic play media that can be found at home and is good for a child's development. The purpose of this activity, which involves empowering cadres, is to spread knowledge about health, one aspect of which is the growth and development of children. The three phases of the activity are preparation (working with cadre leaders and the village), implementation (providing counseling), and evaluation. The activity employs counseling as its method. As a consequence of this exercise, cadres' understanding of child development has increased by 60%, active play techniques by 100%, and simple play media by 80%.